Joint User and Beam Selection in Millimeter Wave Networks - Santosh Kumar Singh; Satyabrata Sahu; Ayushi Thawait; Prasanna Chaporkar; Gaurav S. Kasbekar (IEEE Open Journal of Vehicular Technology)
We investigate the problem of maximizing the sum of the weighted rates of user equipment (UE) by finding a UE and a beam for each access point (AP) for concurrent transmission in millimeter wave (mmWave) networks. We prove that this problem is NP-complete. We propose two algorithms– Markov Chain Monte Carlo (MCMC) based and local interaction game (LIG) based UE and beam selection– and prove that both of them asymptotically achieve the optimal solution. Also, we propose two fast greedy heuristics—NGUB1 and NGUB2—for UE and beam selection. Using detailed simulations, we demonstrate that the performance of our proposed greedy heuristics is close to that of the asymptotically optimal algorithms and superior to that of the most relevant algorithms proposed in prior work.